2011
DOI: 10.1016/j.molcel.2010.12.005
|View full text |Cite|
|
Sign up to set email alerts
|

miR-182-Mediated Downregulation of BRCA1 Impacts DNA Repair and Sensitivity to PARP Inhibitors

Abstract: Expression of BRCA1 is commonly decreased in sporadic breast tumors, and this correlates with poor prognosis of breast cancer patients. Here we show that BRCA1 transcripts are selectively enriched in the Argonaute/miR-182 complex and miR-182 down-regulates BRCA1 expression . Antagonizing miR-182 enhances BRCA1 protein levels and protects them from IR-induced cell death, while overexpressing miR-182 reduces BRCA1 protein, impairs homologous recombination-mediated repair, and render cells hypersensitive to IR. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
277
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(292 citation statements)
references
References 63 publications
10
277
1
4
Order By: Relevance
“…The mechanism that regulates expression of this cluster is not known. miR-182 expression has been shown to be responsive to ionizing radiation (33). Of note, we did not observe changes in miR-183-96-182 following exposure to high levels of zinc (data not shown).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The mechanism that regulates expression of this cluster is not known. miR-182 expression has been shown to be responsive to ionizing radiation (33). Of note, we did not observe changes in miR-183-96-182 following exposure to high levels of zinc (data not shown).…”
Section: Discussionmentioning
confidence: 58%
“…Both miR-96 and miR-182 are reported to target FOXO1 and FOXO3 in breast and melanoma cancer cell lines and endometrial tumors (28,29,39;Myatt,47). mir-182 also targets BRCA1 and may sensitize cells to poly(ADP-ribose) polymerase inhibitors (33). The miR-182 knock-out mouse does not have an apparent phenotype (40), suggesting potential compensation by miR-96 and miR-183.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-182 inhibits expression of BRCA1 [21] that is responsible for repair of double-stranded DNA damage (DSBs) in homologous recombination (HR). Deficiency of BRCA1 protein leads to activation of other than HR repair mechanisms, the inefficiency of which causes genetics instability [22].…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of BRCA1 protein leads to activation of other than HR repair mechanisms, the inefficiency of which causes genetics instability [22]. Moreover, silencing of miR-182-5p resulted in increase of BRCA1 levels and induction of resistance to radiation and to treatment with poly (ADP-ribose) polymerase 1 (PARP-1) inhibitors [21]. This phenomenon could be explained by activation of BR-CA1-related tumor cell repair mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] ncRNAs can also regulate the expression of various DDR genes such as ATM, BRCA1, H2AX, RAD51 and p53. [24][25][26][27][28] In addition, it has been shown that DSBs trigger the expression of ncRNAs (called diRNAs) from sequences surrounding the damage sites. These diRNAs regulate the recruitment of DDR proteins and promote DSB repair.…”
Section: Introductionmentioning
confidence: 99%